2013
DOI: 10.1002/ijc.28581
|View full text |Cite
|
Sign up to set email alerts
|

CD8+tumor-infiltrating lymphocytes at primary sites as a possible prognostic factor of cutaneous angiosarcoma

Abstract: Tumor-infiltrating lymphocytes (TILs) have been reported as a prognostic factor in various cancers and are a promising target for immunotherapy. To investigate whether TILs have any impact on the prognosis of angiosarcoma patients, 55 non-treated patients (40 patients at stage 1 with cutaneous localized tumors, 4 patients at stage 2 with lymph node metastases and 11 patients at stage 3 with distant metastases) with angiosarcoma were evaluated retrospectively by immunohistochemistry stained CD4, CD8, FOXP3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 27 publications
(33 reference statements)
1
59
0
Order By: Relevance
“…We classified patient groups into three stages as reported previously, stage I for patients with local tumors, stage II for patients with lymph node involvement, and stage III for patients with distant metastases. 11,32 Computed tomography (CT) was used to detect metastasis of lymph nodes and distant organs. 11 out of 106 samples were taken after systemic treatments including taxanes and pasopanib.…”
Section: Patient Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified patient groups into three stages as reported previously, stage I for patients with local tumors, stage II for patients with lymph node involvement, and stage III for patients with distant metastases. 11,32 Computed tomography (CT) was used to detect metastasis of lymph nodes and distant organs. 11 out of 106 samples were taken after systemic treatments including taxanes and pasopanib.…”
Section: Patient Samplesmentioning
confidence: 99%
“…Fujii et al reported that antitumor immunity with CD8 C T cells in tumor-infiltrating lymphocytes (TILs) is important to prevent the progression of CAS. 11 Certain types of human cancers express programmed cell death-1 ligand-1 (PD-L1) on the cell surface, which enables cancer cells to escape immune reactions by binding the inhibitory receptor programmed cell death-1 (PD-1) on T cells. 12 Clinically, tumor PD-L1 expression affects patients' prognosis, and anti-PD-1-antibody administration has shown significant efficacy in treating several malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…12 Patients with immune deficiencies, such as organ transplant patients, show an increased incidence of sarcomas. 13 Lymphocytic infiltration of the tumor was demonstrated in sarcomas, with positive prognostic value in cutaneous angiosarcomas, 14 negative prognostic value in STS or liposarcomas, 8,[15][16][17][18][19] or no prognostic value in MPNST. 20 An unfavorable prognostic role of tumor-associated macrophages was reported in leiomyosarcomas 21 and myxoid liposarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…Fujii et al characterized the T cells found in cutaneous angiosarcoma. 26 Both CD4 and CD8 T cells were identified in all tumors, including FoxP3 positive cells which may represent regulatory T cells. Higher frequencies of CD8 T cells were associated with improved overall and distant metastasis-free survival.…”
Section: Sts Subtype Heterogeneitymentioning
confidence: 93%